Optimization of Lead Removal from Aquoeus Solution Using Iron Oxide-Modified Alumina Adsorbent Incorporating Sapodilla Leaf Extract - Ulhusna, Annisa; Toemen, Susilawati; Salamun, Nurrulhidayah (Journal of Agriculture, 2025)
In this study, a novel adsorbent material, alumina beads modified with iron oxide and Sapodilla leaves extract (Fe/C/Al?O?), was successfully synthesized and evaluated for its efficiency in remediating lead [Pb (II)] ions from aqueous solutions. To determine the optimal removal conditions, the adsorption performance was investigated under varying operational parameters, including initial Pb (II) concentration, adsorbent dosage, and contact time. The best removal efficiency was achieved at an initial Pb (II) concentration of 60 mg L?¹, with an adsorbent dosage of 1.5 g and a contact time of 30 minutes, resulting in a high Pb (II) removal rate of 97.75%. Comprehensive characterization of the Fe/C/Al?O? adsorbent was conducted using X-ray diffraction (XRD) to determine crystalline structure, nitrogen adsorption–desorption analysis (NA) for surface area and porosity evaluation, field emission scanning electron microscopy (FESEM) to observe surface morphology, energy-dispersive X-ray spectroscopy (EDX) for elemental composition analysis, and Fourier transform infrared spectroscopy (FTIR) to identify functional groups involved in adsorption. The adsorption data fit the Langmuir isotherm model, indicating monolayer adsorption with a maximum sorption capacity (qmax) of 4.23 mg g?¹. Kinetic studies revealed that the Pb (II) uptake process followed a pseudo-second-order kinetic model, suggesting chemisorption as the dominant mechanism. These findings highlight the potential application of Fe/C/Al?O? as an effective and eco-friendly adsorbent for heavy metal removal in wastewater treatment.